Quel avenir pour le logement social en Tunisie ? - Sami Ben Fguira; Mongi Belarem (Confins)
Since independence, social housing has constituted an important dimension in Tunisia and a challenge for the maintenance of social peace. As a result, this sector remained a major concern of the various development policies adopted. However, this offer has often been aimed at the solvent and ignorant population classes. The inadequacy of housing for the lower classes in urban areas has led to urban dysfunctions in Tunisian cities. There was a proliferation of spontaneous habitat, a rise in poverty and an accentuation of the phenomena of socio-spatial segregation. This has imposed new challenges for urban planning in Tunisia. Today, urban development implies in the first place the recognition of the rights of the working classes in the city. It is a matter of placing the needs and interests of the vulnerable layers at the same level as those of the solvent layers in terms of housing policies and legislation. However, like other developing countries, Tunisia is confronted with a new contradictory circumstance: on the one hand, globalization and its neo-liberal agenda implying the abandonment of a certain number of fields of social action, and on the other hand, the need to cope with the excessive social demands induced by the revolution through voluntarist housing policies aimed in particular the working classes.It is a matter of placing the needs and interests of the vulnerable classes at the same level as those of the solvent ones in terms of housing policies and legislation.